2009
DOI: 10.17221/61/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of dough made from grain amaranth-cereal composite flours based on wheat and spelt

Abstract: Grobelnik Mlakar S., Bavec M., Turinek M., Bavec F. (2009): Rheological properties of dough made from grain amaranth-cereal composite flours based on wheat and spelt. Czech J. Food Sci., 27: 309-319.The purpose of this study was to investigate the effect of the addition of amaranth wholegrain flour on the rheological characteristics of wheat and spelt flour dough. Organically produced composite flours made from basic flours of wheat (refined) or spelt (refined, wholegrain) and amaranth flour in the propostions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Higher water absorption (53.0–64.4%) of spelt flour was reported by Bojňanská and Frančáková (2002). Wheat flour was generally characterized by higher water absorption (56.4%) than spelt flour, whereas contrary results were reported by Grobelnik Mlakar et al (2009). The lowest water absorption (52.6% on average) was found in Belgian spelt varieties.…”
Section: Resultsmentioning
confidence: 69%
“…Higher water absorption (53.0–64.4%) of spelt flour was reported by Bojňanská and Frančáková (2002). Wheat flour was generally characterized by higher water absorption (56.4%) than spelt flour, whereas contrary results were reported by Grobelnik Mlakar et al (2009). The lowest water absorption (52.6% on average) was found in Belgian spelt varieties.…”
Section: Resultsmentioning
confidence: 69%
“…Pseudocereal amaranth is a gluten-free grain and its addition in composite flour in the bread-making process is a challenge. Some authors demonstrated that less than 20% amaranth replacement positively influenced bread physical parameters, especially the loaf volume, due to the reduction of gluten content in composite flour [7,8]; however, Burisova et al [9] and Miranda-Ramos et al [3] showed that amaranth content higher than 20% decreased the content of gluten and had a negative effect on the dough quality (adhesiveness) and bread (low volume and flavor). In recent years, a considerable number of researchers have also focused on highlighting the technological benefits that the addition of pseudocereals brings to bread when innovative manufacturing techniques are employed (e.g., reduction of particle size and use of sourdough) and adequate proportions of pseudocereals are used [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nutritional improvement (Shahzadi et al . 2005; Grobelnik Mlakar et al . 2009; Boye et al .…”
Section: Introductionmentioning
confidence: 99%